2022
DOI: 10.1097/bsd.0000000000001301
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Bone Morphogenetic Protein 2 Throughout the United States

Abstract: Study Design: Retrospective Database Study. Objective: Investigate utilization of bone morphogenetic protein (BMP-2) between 2004 and 2014. Summary of Background Data: The utilization, particularly off-label utilization, of BMP-2 has been controversial and debated in the literature. Given the concerns regarding cancer and potential complications, the risk benefit profile of BMP must be weighed with each surgical case. The debate regarding the costs and potential side effects of BMP-2 compared with autologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Respondents may have been more likely to participate due to being advocates for rhBMP2 usage, or they may be individuals who are staunchly against the off-label use. We did observe a response rate of 20.5%, which is similar to prior studies [ 14 ]. Furthermore, the relatively low number of respondents is a limitation of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respondents may have been more likely to participate due to being advocates for rhBMP2 usage, or they may be individuals who are staunchly against the off-label use. We did observe a response rate of 20.5%, which is similar to prior studies [ 14 ]. Furthermore, the relatively low number of respondents is a limitation of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Hofstetter et al found that the frequency of complications from rhBMP-2 rose with increasing dosages used [ 13 ]. Importantly, the rate of rhBMP-2 use in the United States has been reported to be declining steadily since 2008, possibly due to the reports of possible associated adverse effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, the application of these growth factors remains limited and challenging due to high prices, the control of physiological doses, and poor clinical outcomes. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Because the quality of autograft in osteoporosis patients is poor, other bone substitutes have been adopted for spine fusion, such as allograft, demineralized bone matrix, and growth factors. Recombinant human bone morphogenic protein 2 (BMP-2) stimulates bone growth through a number of pathways, including stimulation of mesenchymal stem cell differentiation down an osteoblastic lineage, and now has become the important surgical option, especially in severe osteoporotic patients [ 6 , 7 ]. Many studies have demonstrated the utility of recombinant human BMP-2 (rhBMP-2) in enhancing fusion rates, so the use of rhBMP-2 has expanded in an off-label manner for various spinal fusion surgeries to assist with fusion in severe osteoporosis patients.…”
mentioning
confidence: 99%
“…Recombinant human bone morphogenic protein 2 (BMP-2) stimulates bone growth through a number of pathways, including stimulation of mesenchymal stem cell differentiation down an osteoblastic lineage, and now has become the important surgical option, especially in severe osteoporotic patients. 6,7 Many studies have demonstrated the utility of recombinant human BMP-2 (rhBMP-2) in enhancing fusion rates, so the use of rhBMP-2 has expanded in an off-label manner for various spinal fusion surgeries to assist with fusion in severe osteoporosis patients. However, there is a significant relation between the dose of rhBMP-2 use and the complication rates.…”
mentioning
confidence: 99%